The originality of onymic means in the dramatic texts of the theater of the absurd by Dmitry Lipskerov - Petrachkova, Inna M. (Journal of the Belarusian State University. Philology, 2021)
The article is devoted to the study of the proper names system in the context of the dramatic works of the new wave. It examines the whole collection of poetic names that function in the plays of the popular Russian playwright of the late 20th century Dmitry Mikhailovich Lipskerov. The subject of study is the onymic means of the proprietary space of six of his plays during the period 1980–90s, in the paradigmatic, pragmatic, statistical and semantic-stylistic aspects. The study aims at identifying general patterns of the onomasticon of postmodern drama. The main purpose of the work is to determine the specificity of onymic means, the types of names, onomastic classes, modifiers, functions of poetry names and to describe their semantic and stylistic features, due to the era of the creation of the work and the artistic method chosen by the D. M. Lipskerov, as well as to reveal certain onomastic universals characteristic of creativity playwright of postmodernism. Today, in literary onomastics, there are no complex studies related to the study of the onomasticon of modern Russian drama, which would reflect the main trends and directions in its development. The works of drama are constantly updated and replenished: absorb the socio-cultural attitudes that exist in society at a certain historical stage. Of course, when choosing onyms for a dramatic creation, the author is guided by them, relying on the prevailing worldview moods and stereotypes. The gap closure problem in the development of relatively new works of writers in various aspects, including from the point of view of onomapoetic analysis, will always be relevant, fresh and interesting for modern philological sciences. The poetonymoshere of the Russian theater of postmodernism, including the plays of D. M. Lipskerov, has also not been previously studied, but meanwhile it occupies a special place and plays an important role in understanding the theoretical foundations of literary onomastics and their further development. The materials of onomastic research, reflected in the article, will find practical application in the research and teaching activities of literary scholars and linguists.